(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
In this paper we consist the problem of Couette flow between two horizontal parallel porous flat plates of an electrically conducting viscous incompressible fluid. The stationary plate is subjected to a transverse sinusoidal injection of the fluid and its corresponding removal by the constant suction through the other plate, in uniform motion and because of injection velocity the flow becomes three-dimensional. A magnetic field of uniform strength is applied normal to the planes of the plates. The effect of injection/suction velocity and the magnetic field on the flow field, skin friction and heat transfer are reported and discussed in detail.